2022
DOI: 10.1139/gen-2022-0040
|View full text |Cite
|
Sign up to set email alerts
|

miR-181a-5p is a potential candidate epigenetic biomarker in multiple sclerosis

Abstract: Multiple Sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) characterized by demyelination and axonal degeneration. Abnormal expression of microRNAs (miRNA) plays an important role in MS pathology. In this cohort study, differential expression of the four miRNAs (<i>hsa-miR-155-5p</i>, <i>hsa-miR-9-5p</i>, <i>hsa-miR-181a-5p</i>, and <i>hsa-miR-125b-5p</i>) were investigated in 69 individuals, including 39 MS patients (relapsing-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The current body of literature demonstrates the altered expression of the miR-181 family in neurodegenerative disorders, including MS, Parkinson's disease, and Alzheimer's disease (32). Quantitative real-time PCR (qPCR) of PBMCs identi ed miR-181a-5p and miR-181b-5p as differentially downregulated and upregulated miRNAs, respectively, in MS patients (33,34). Moreover, targeting genes involved in neuroin ammation, such as MAP2K1, CREB1, ATXN1, and ATXN3, by miR-181a-5p re ects its therapeutic potential (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current body of literature demonstrates the altered expression of the miR-181 family in neurodegenerative disorders, including MS, Parkinson's disease, and Alzheimer's disease (32). Quantitative real-time PCR (qPCR) of PBMCs identi ed miR-181a-5p and miR-181b-5p as differentially downregulated and upregulated miRNAs, respectively, in MS patients (33,34). Moreover, targeting genes involved in neuroin ammation, such as MAP2K1, CREB1, ATXN1, and ATXN3, by miR-181a-5p re ects its therapeutic potential (34).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR (qPCR) of PBMCs identi ed miR-181a-5p and miR-181b-5p as differentially downregulated and upregulated miRNAs, respectively, in MS patients (33,34). Moreover, targeting genes involved in neuroin ammation, such as MAP2K1, CREB1, ATXN1, and ATXN3, by miR-181a-5p re ects its therapeutic potential (34). The expression of miR-181c-5p is reported to be misregulated in PBMCs, cerebrospinal uid (CSF), and serum of relapsing-remitting multiple sclerosis (RRMS) patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ROC analysis allowed distinguishing RRMS from SPMS/PPMS patients with AUC values for miR-433-3p, miR-432-5p, and miR-485-5p were 0.93, 0.86, and 0.87, respectively ( Ebrahimkhani et al, 2017 ). The recent study by Edgünlü et al (2022) showed that the expression of miR-181a-5p was downregulated and associated with an increased risk of MS ( p = 0.012). Furthermore, in silico analyses showed that circulating miR-181a-5p can participate in MS pathology by targeting genes involved in inflammation and neurodegeneration molecular pathways, such as MAP2K1, CREB1, ATXN1, and ATXN3 ( Edgünlü et al, 2022 ).…”
Section: The Concept Of Mirna As a Biomarker For Msmentioning
confidence: 99%
“…The recent study by Edgünlü et al (2022) showed that the expression of miR-181a-5p was downregulated and associated with an increased risk of MS ( p = 0.012). Furthermore, in silico analyses showed that circulating miR-181a-5p can participate in MS pathology by targeting genes involved in inflammation and neurodegeneration molecular pathways, such as MAP2K1, CREB1, ATXN1, and ATXN3 ( Edgünlü et al, 2022 ).…”
Section: The Concept Of Mirna As a Biomarker For Msmentioning
confidence: 99%